Role of Tight Glycemic Control during Acute Coronary Syndrome on CV Outcome in Type 2 Diabetes - Ferdinando Carlo Sasso; Luca Rinaldi; Nadia Lascar; Aldo Marrone; Pia Clara Pafundi; Luigi Elio Adinolfi; Raffaele Marfella (Journal of Diabetes Research)
Both incidence and mortality of acute coronary syndrome (ACS) among diabetic patients are much higher than those among nondiabetics. Actually, there are many studies that addressed glycemic control and CV risk, whilst the literature on the role of tight glycemic control during ACS is currently poor. Therefore, in this review, we critically discussed the studies that investigated this specific topic. Hyperglycemia is implicated in vascular damage and cardiac myocyte death through different molecular mechanisms as advanced glycation end products, protein kinase C, polyol pathway flux, and the hexosamine pathway. Moreover, high FFA concentrations may be toxic in acute ischemic myocardium due to several mechanisms, thus leading to endothelial dysfunction. A reduction in free fatty acid plasma levels and an increased availability of glucose can be achieved by using a glucose-insulin-potassium infusion (GIKi) during AMI. The GIKi is associated with an improvement of either long-term prognosis or left ventricular mechanical performance. DIGAMI studies suggested blood glucose level as a significant and independent mortality predictor among diabetic patients with recent ACS, enhancing the important role of glucose control in their management. Several mechanisms supporting the protective role of tight glycemic control during ACS, as well as position statements of Scientific Societies, were highlighted.